Оптимизация режимов электроискрового диспергирования металлических гранул в жидкости по распределению энергии, выделившейся в элементах разрядной цепи - Листовский, Дмитрий Игоревич; Петриченко, Сергей Викторович (НТУ "ХПИ", 2016)
Предложена методика определения начальных условий реализации разряда в гранулированном слое для оптимизации распределения энергии в элементах разрядной цепи установок объемного электроискрового диспергирования. Проведена экспериментальная проверка расчетных выражений для оценки амплитуд разрядных токов при реализации разряда в реакторе с большим количеством металлических гранул, показаны способы определения эмпирических коэффициентов и предложен способ масштабирования их значений для различных геометрических характеристик реактора и гранул.

Problem of the energy efficiency increase of the equipment for volume electro spark dispersion of metal granules in liquid was addressed. Dynamic dependencies of discharge currents on discharge circuit’s parameters were formalized. Methods of definition of initial conditions of the granulated layer discharge implementation for the optimization of energy distribution in elements of volume electro spark dispersion installations discharge circuit were offered. Calculated expressions for discharge current amplitude’s estimation during discharge realization in the reactor with a large number of metal granules were experimentally approbated. Methods of definition of empirical coefficients were shown and the method of scaling of their values for different geometrical characteristics of the reactor and granules was offered.
Electrospark dispersion of metal granules regimes’ optimization on distribution of energy released in discharge circuit elements
Keywords: объемное электроискровое диспергирование; реактор диспергирования; слой гранул; двухконтактная модель; межэлектродный промежуток; контакт между гранулами; dispersion reactor; double-contact model; inter electrode gap; contact between granules